BUSINESS PLAN OF PAWVILLION PARADISE: ONE-STOP PET CAFÉ, CARE & PLAYGROUND EXPERIENCE IN THE CITY OF BANDUNG - Rezka Randytia Rahardjo, Muhammad; Hendri, Meriza (Syntax Literate, 2026)
The rapid growth of pet ownership in urban areas has transformed pets into family members, increasing demand for high-quality, integrated pet-related services. However, pet cafés, grooming services, and playground facilities in Indonesia remain fragmented, requiring pet owners to visit multiple locations. This study aims to design and evaluate a one-stop pet lifestyle business model that integrates a pet-friendly café, professional pet care services, and recreational playgrounds in a single destination. The research applied a business planning approach using Design Thinking, Lean Canvas, Business Model Canvas (BMC), and SWOT analysis. Data were collected through market observation, industry trend analysis, and financial projections. Business feasibility was assessed using financial indicators such as Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period, and Profitability Index, supported by the Timmons Entrepreneurial Model. The results indicate that the integrated concept of PAWvillion Paradise successfully addresses urban pet owners’ needs for convenience, hygiene, safety, and emotional bonding with their pets. The SWOT analysis places the business in Quadrant I (Growth Strategy), indicating strong internal capabilities and favorable market opportunities. Financial projections show positive cash flow from the first year, a payback period of approximately 3.06 years, and an IRR of 88.11%, demonstrating strong financial feasibility. In conclusion, PAWvillion Paradise represents a viable and sustainable business model that responds to urban lifestyle trends and promotes animal welfare. The integrated service concept enhances customer experience while providing a competitive advantage in the growing pet industry market in Bandung, Indonesia.